(3MjGJjs (3bUI aJi ef GdQjas - (3JTjNha, CfWhfs; (3GdTfjWj, eMehOs ((3GdbGgQIs (3CbdGe YQHjI ddfTQ hGdJhRjYs, 2021)
(3GTJgQ CfWhf JTjNha Hchfg CYXe cGJH bUI bUjQI Ydi GdEWdGb, hcGf CjkVG CSJGkPG aj GdQhGjI(B. (3hcGfJ CcKQ EHOGYGJg cJGHg GdTjb GdeeJY (B""(3MjGJj(B"" (3hgj JUhQ bUI TGH eJeQO jTYQ HGdGTeFRGR GdTOjO ef GdeLJeY GdHQLhGRj dOQLI Cfg jJNdi Yf GdYjT hSW GdWHbGJ GdYGedI, abW djLO faSg aj ehGLgI GdBKGQ GdbGJdI CNdGbjG hPgfjG ddMjGI GdQjajI(B. (3hgj CjkVG YHGQI Yf JYdjb LRFj Ydi adSaI JhdSJhj, hHgG LGfH ef GdSjQI GdPGJjI eHfj Ydi NdajI eOjfI JTjNha GdUZjQI(B. (3hdcf GdCge ef Pdc, CfgG JHQR JTjNha aj ChL UhQg, YGQVG cd fbGW bhJg GdTgjQI; TNUjGJ MjI, hJaGUjd eMOhOI hdcf eYHQI, hedGMXI faSjI QGFYI, hCMO CcKQ ehVhYGJg EKGQI; fVGd GdTHGH ddMaGX Ydi GdeKGdjI VO GdYRdI GdeJRGjOIs
Keywords: (3GdCOH GdQhSjs